Thymic neuroendocrine tumour in multiple endocrine neoplasia type 1: female patients are not rare exceptions. (7th January 2013) - Sakurai, Akihiro; Imai, Tsuneo; Kikumori, Toyone; Horiuchi, Kiyomi; Okamoto, Takahiro; Uchino, Shinya; Kosugi, Shinji; Suzuki, Shinichi; Suyama, Keiko; Yamazaki, Masanori; Sato, Ai
Summary Objective Thymic neuroendocrine tumour (Th‐NET) occurs in 2–5% of patients with MEN1 and has high malignant potency accompanying recurrence and distant metastasis. While Th‐NET is recognized to develop predominantly in men and heavy smokers, a number of female patients have been reported in the literature. The objective of this study is to clarify the clinical features of MEN1 patients with Th‐NET using database analysis. Design/Patients Clinical data of patients with Th‐NET were extracted and analysed from a recently constructed database of Japanese MEN1 patients. Results Among 560 registered cases, Th‐NET was seen in 28 (5·0%) patients. Of note, 36% of patients (10/28) were women; only one patient among those was a smoker and another six patients were non‐smokers. Age at diagnosis of Th‐NET and MEN1, tumour size, prevalence of other MEN1‐related tumours did not differ between male and female patients, and 10‐year survival probability was 0·271 ± 0·106. Conclusions Although the prevalence of Th‐NET in women (3·2%) is significantly lower than that in men (7·6%), a considerable proportion of female patients develop Th‐NET. Given that Th‐NET is a major determinant of life expectancy of patients, our results alert clinicians who treat patients with MEN1 that surveillance of Th‐NET is essential even for female patients without a smoking habit.